Implementasi Kebijakan Perizinan Berusaha Berbasis Resiko Dalam Upaya Mempermudah Pengurusan Perizinan Pelaku Usaha UMKM di Kecamatan Kalideres Kota Administrasi Jakarta Barat - Saprudin, Mohamad; Irawan, Bambang (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2025)
This study aims to assess the implementation of the Risk-Based Business Licensing Policy for business actors in the sector of Micro, Small, and Medium Enterprises (MSMEs) in Kalideres District, West Jakarta Administrative City. The analysis of the implementation is based on George Edward III’s implementation theory, which includes the following indicators: Communication, Resources, Disposition, and Bureaucratic Structure. The research method employed is a descriptive qualitative approach. Data collection techniques used in the study include interviews, observations, and documentation. The results of this study show that the implementation of the policy has not been fully effective; communication has not been adequately established; human resources and budget allocation are considered insufficient in terms of quantity; disposition has been relatively positive, as demonstrated by the attitude and commitment of the officers; and the bureaucratic structure is in accordance with the established procedural framework. Challenges encountered in the implementation of the policy include: MSME business actors’ limited understanding of the risk-based business licensing process, technical issues with the licensing application system, complicated licensing requirements, uneven socialization efforts for MSME business actors, and the lack of time available for the business actors to process business licenses at the sub-district office. Efforts undertaken by the One-Stop Integrated Investment and Services Management Unit (UP PMPTSP) of Kalideres District and its staff to address these challenges include: coordinating with relevant stakeholders, conducting direct socialization in public spaces such as the Integrated Child-Friendly Public Space (RPTRA) and RW Offices, organizing public service week activities in public spaces, conducting online socialization via platforms such as WhatsApp groups, and establishing a complaint service through a call center at the business service outlets.